Satisfaction of nursing students with two clinical evaluation methods: objective structured clinical examination (OSCE) and practical examination of clinical competence - Bolourchifard, F; Neishabory, M; Ashketorab, T; Nasrollahzadeh, Sh (Advances in Nursing & Midwifery, 2010)
Background and aim Clinical training is an essential part of nursing education. Its evaluation can deeply affect on its quality and has always been a challenge for nursing education. The aim of this descriptive study was to compare satisfaction of nursing students with two methods of clinical evaluation, namely, objective structured clinical examination (OSCE) and practical examination in faculty of nursing and midwifery affiliated to Shahid Beheshti University of Medical Sciences in Tehran in 2007. Materials and Methods 44 sophomore students in their orthopedic clinical training were selected by convenience sampling method and evaluated by the two evaluation methods. Data were collected by a satisfaction questionnaire in 3 cognitive, affective, and psychomotor domains. Content and inter-rater methods were used for validity and reliability of the questionnaire respectively. SPSS package (ver. 13) was used for data analysis. Findings Satisfaction rates of nursing students in the 3 domains were higher in OSCE than in practical examination with a significant difference in achieving educational goals in the domains and in total (P<0.001). Conclusion In this study, OSCE was used in this group of students for their clinical training for the first time. It seems that this type of evaluation may better satisfy nursing students in their clinical training. Keywords: Objective Structured Clinical Examination (OSCE), Practical examination, Satisfaction of students. *Corresponding Author: Bolourchifard, Fariba. Lecturer, Dept. of Medical-Surgical Nursing, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences, Tehran, Iran. E-mail: Bolourchi@sbmu.ac.ir